Assessment in CLIL: Test development for content and language for teaching natural science in English as a foreign language - Johanna P. Leal (Universidad de La Sabana, 2016)
On-going bilingual programs without regard to needs analysis; little research on the actual effects of CLIL in Colombia and vague awareness or knowledge about the necessary considerations for effective CLIL programs, underpin the need to address a particular issue of curriculum as it is summative assessment. This small scale study takes place in a Natural Science class using a CLIL approach with thirdgrade students at A2 proficiency level who have been progressively immersed in a bilingual program at a private school in Bogotá, Colombia. Regularly scheduled tests were analyzed in order to identify suitable assessment items hat simultaneously report on the content and language achievement in order to provide guidelines for test development that are aligned with the teaching goals, consistently measure students' progress, and facilitate teaching practices. This study entails a systematic examination of test items using formal item analysis to depict test validity from an assessment grid that integrates content, at different knowledge levels, CALP functions and cognitive skills. The study concludes that the assessment grid is a helpful tool to discriminate language and content achievement in the results of multiple-choice CLIL tests, by increasing teachers' understanding of the language demands of test items and the level of difficulty of content tasks.   doi: 10.5294/laclil.2016.9.2.3